An Overview of Nigeria and Morocco Bilateral Relations under Buhari’s Administration - Stephen, Rwang Patrick; Pindiga , Hussaini Ahmed; Abubakar, Anas (Kashere Journal of Politics and International Relations, 2025)
The Bilateral relationship between states has remained a pathway to national development over the years. Nigeria and Morocco has a lot of things in common ranging from religion to economic frontiers. Trade between states is central to fostering of relationships. This paper examine the conceived trade relationship of the Buhari administration (2015-2023) which is in line with it Foreign Policy path between the Kingdom of Morocco and Nigeria in an attempt to make gas scarcity in Africa a thing of the past and create job opportunities to youths across the continent. The authors investigate the relevance of the project and advised government of the states involved to complete it despite all odds for the benefit of their citizens and for the growth off their state’s economy. The paper makes use of secondary methods of data collection to sort materials from books, writings, newspapers and journals. Elite theory was adopted to show how elites will carry out any policy they feel will be beneficiary to their states. The conclusion was, since the Buhari administration left office without concluding the pact; the Tinubu led administration should complete the project in earnest for the good of the nation.